Penerapan metode preview, question, read, reflect, recite, and review (pq4r) untuk meningkatkan keterampilan membaca pemahaman pada peserta didik kelas iv sekolah dasar - Anindhita Citra Yasminta; Siti Wahyuningsih; Hadiyah Hadiyah (Universitas Sebelas Maret, 2019)
Abstract. The aim of this research is to improve reading comprehension skills through application Preview, Question, Read, Reflect, Recite, and Review (PQ4R) method to fourth grade students of SD N Geneng 02 Sukoharjo 2018 to 2019 school year. This type of research is a Classroom Action Research that is conducted in three cycles which consists of four stages; planning, action, observation, and reflection. The subjects of this study are teachers and fourth grade students of SD N Geneng 02 Sukoharjo. The technique of collecting data are observation, interviews, tests, and documentations. The validity test uses triangulation techniques, source triangulation, and content validity. Analysis of the data used in this study is an interactive analysis technique which has four steps. They are collecting data, reduction data, presentation, and conclusion. The results showed that the average score of pre-action class scores of 51,41 with 13,64% classical completeness, increased to 61,96 with 34,64% classical completeness in the first cycle and increased to 72,32 with a classical completeness of 63,64% in cycle II, and increased again to 78,52 with a classical completeness of 91,30% in cycle III. Based on the results of the study, it can be concluded that through the application of the Preview, Question, Read, Reflect, Recite, and Review (PQ4R) method can improve reading comprehension skills of fourth grade students of SD N Geneng 02 Sukoharjo in 2018 to 2019 school year.